Interaction of Single Cells with 2D Organic Monolayers: A Scanning Electrochemical Microscopy Study. Issue 20 (17th August 2018) - Bartolini, Luca; Malferrari, Marco; Lugli, Francesca; Zerbetto, Francesco; Paolucci, Francesco; Pelicci, Pier Giuseppe; Albonetti, Cristiano; Rapino, Stefania
Abstract: Cell shape is a valuable indicator of cell health status and interactions with the extracellular materials. With the aim to investigate how individual cells respond to chemical microenvironments, we employed 2D monomolecular layers of small organic molecules, characterized by very low roughness. MCF10A cells were grown on these surfaces and characterized by using scanning electrochemical microscopy. The single cell morphologies were analyzed to define a "figure of merit" for the different cell–surface interactions. Such "figure of merit" quantifies the interaction with the microenvironment. This method is applicable to any cell state (metastatic, physiological or pathological) and any surface. Abstract : Character building : Scanning electrochemical microscopy and simple geometrical descriptors are used to characterize cell status. Single cells are characterized to determine the interactions they establish with the surface where they adhere. The regime of cell‐substrate interaction can be assigned.